2021
DOI: 10.1021/acs.jpcb.0c10691
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic Consequences of Host–Guest Interactions; Noncovalent Chlorine Isotope Effects

Abstract: Although weak intermolecular interactions are the essence of most processes of key importance in medicine, industry, environment, and life cycles, their characterization is still not sufficient. Enzymatic dehalogenations that involve chloride anion interaction within a host–guest framework is one of the many examples. Recently published experimental results on host–guest systems provided us with models suitable to assess isotopic consequences of these noncovalent interactions. Herein, we report the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…To deconvolute and better understand the role of both C-H/D hydrogen bond donor polarity and solvent on the DEIE of Cl À binding in these receptors, a systematic study of these two variables would be required, similar to those previously reported, which we intend to pursue in future work. 14,27,28 Analysis of the data for competitive titrations of 2 H/D with Br À revealed no DEIE at any of the tracked 13 C NMR signals; however, each calculated DEIE has a relatively large percent error (0.99-4.64%, compared to 0.20% for the DEIE of Cl À binding), which could potentially obscure small DEIEs. We attribute these large percent errors to a limitation in the Perrin method that assumes that the hosts are fully bound by guest at saturation.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…To deconvolute and better understand the role of both C-H/D hydrogen bond donor polarity and solvent on the DEIE of Cl À binding in these receptors, a systematic study of these two variables would be required, similar to those previously reported, which we intend to pursue in future work. 14,27,28 Analysis of the data for competitive titrations of 2 H/D with Br À revealed no DEIE at any of the tracked 13 C NMR signals; however, each calculated DEIE has a relatively large percent error (0.99-4.64%, compared to 0.20% for the DEIE of Cl À binding), which could potentially obscure small DEIEs. We attribute these large percent errors to a limitation in the Perrin method that assumes that the hosts are fully bound by guest at saturation.…”
mentioning
confidence: 98%
“…binding in these hosts. 13 Because isotope effects, both equilibrium and kinetic, originate solely from changes in the vibrational energy of the isotopically labelled bond, the EIE arising from this study came from changes in the vibrational energies of the bonds in the supramolecular hosts when participating in hydrogen bonding with Cl À isotopes. Indeed, a linear relationship was observed between the hydrogen bond donor (D) D-H bond lengths in the host-guest complex and the computed 35/ 37 Cl EIE.…”
mentioning
confidence: 98%
See 3 more Smart Citations